THE EFFECT OF LONG STORAGE ON MANGROVE (Sonneratia caseolarisi) FRUIT SLICE JAM ON TOTAL PLATE COUNT (TPC) VALUE AND ANTIOXIDANT ACTIVITY - Maharani, Rossa; Pangestu, Chandra Trisna; Andriyono, Sapto; Saputra, Eka (Jurnal Perikanan Unram, 2025)
The mangrove apple (Sonneratia caseolarisi) has potential as an alternative food source due to its high nutritional and antioxidant content. This study aims to analyze the effect of storage duration on mangrove apple-based fruit slices' microbiological and chemical quality by adding rosella extract, focusing on Total Plate Count (TPC) value, antioxidant activity, and proximate analysis. The slices were made by adding 50% rosella extract based on the weight of the fruit pulp and were tested during storage at 0, 7, 14, 21, and 28 days. The research methods included TPC testing to count microorganisms, antioxidant activity testing using the DPPH method, and proximate analysis to determine moisture, fat, protein, ash, and carbohydrate content. The results showed that TPC values increased significantly with longer storage time, with the highest increase in the fourth week. Antioxidant activity also decreased over time, indicating the degradation of antioxidant compounds due to oxidation. Proximate testing revealed increased moisture and fat content, while protein, ash, and carbohydrate levels decreased as storage duration increased.